Strain Release in Hydrogen Atom Transfer from 1,4-Disubstituted Cyclohexanes to the Cumyloxy Radical - Galeotti, Marco; Palone, Andrea; Salamone, Michela; Liu, Fengjiao; Yu, Yanmin; Houk, K. N.; Bietti, Massimo (Synlett, 2025)
A kinetic, product, and computational study on the reactions of the cumyloxyl radical (CumO•) with 1,4-dimethyl- and 1,4-diphenylcyclohexanes is reported. The rate constants for hydrogen atom transfer (HAT) from the C–H bonds of these substrates to CumO•, together with the corresponding oxygenation product distributions reveal the role of strain release on reaction site selectivity. Transition structures and activation barriers obtained by DFT calculations are in excellent agreement with the experimental results. Tertiary/secondary ratios of oxygenation products of 0.6, 1.0, and 3.3 were observed, for trans-1,4-dimethyl-, cis-1,4-dimethyl-, and trans-1,4-diphenylcyclohexane, respectively. With cis-1,4-diphenylcyclohexane, exclusive formation of the diastereomeric tertiary alcohol products was observed. Within the two diastereomeric couples, the tertiary equatorial C–H bond in the cis- isomer is ca. 6 and 27 times more reactive, respectively, than the tertiary axial ones, a behavior that reflects the release of 1,3-diaxial strain in the HAT transition state. The tertiary axial C–H bonds of the four substrates show remarkably similar reactivities in spite of the much greater stabilization of the benzyl radicals resulting from HAT from the 1,4-diphenylcyclohexanes. The lack of benzylic acceleration is discussed in the framework of Bernasconi’s ‘principle of nonperfect synchronization’.
Keywords: hydrogen atom transfer; alkoxyl radicals; C–H bond functionalization; strain release; torsional effects; nonperfect synchronization